Nitrate Removal on a Cu/Cu2O Photocathode under UV Irradiation and Bias Potential - Paschoal, Fabiana Maria Monteiro [UNESP]; Nuñez, Luciana [UNESP]; De Vasconcelos Lanza, Marcos Roberto; Zanoni, Maria Valnice Boldrin [UNESP] (My University, 2013)
The present work describes a suitable method for treatment of water contaminated with nitrate by using a photoelectrochemical method. A Cu/Cu 2O electrodeposited electrode is used as photocathode with long-term stability under UV irradiation and applied potential of +0.2 V vs Ag/AgCl. In this condition 93% of nitrate is removed after 75 min of photoelectrolysis conducted in NaCl 0.07 mol L-1 and pH = 7. Nitrate reduction on Cu/Cu2O photoelectrodes occurs in the cathodic compartment cell via electrons generated under UV irradiation, as expected for a p-type electrode leading to 42% of remaining nitrite and 52% gaseous nitrogen derived, respectively. ©2013 Science & Technology Network, Inc.
Keywords: Cu/Cu2O electrode; Nitrate reduction; Nitrogen selectivity; Photoelectrocatalytic reduction